Einfluss von Hochleistungssport auf den Energiestoffwechsel - Schmidt, W.; Maassen, N. (Wiener Medizinische Wochenschrift, 1998)
The knowledge about metabolism and muscular fatigue has been considerably improved during the recent years. Intramuscular pH should not generally be discussed as a factor of cellular fatigue as it has been shown to increase transiently at the beginning and to be very differently affected in ST-(6,9) and FT-fibers (6,2) at the end of exercise. During maximum exercise, we assume changes of muscle membrane potential due to increasing interstitial potassium concentrations as an important performance-limiting factor. The role, lactate is playing during exercise, has to be thought over. Its production by the binding of two protons to the pyruvate molecule is necessary for an intensive anaerobic and aerobic metabolism. The lactate molecules itself represent a source of energy, which is preferentially used by the heart muscle and by ST-fibers working at lower intensity. During long term endurance events, the glycogen stores are assumed to be a limiting factor. However, no direct casual relationship between glycogen and fatigue mechanisms has been found hithertoo. The anaerobic glycolytic metabolism decreases during long lasting exercise as a result of lowered glycogen stores. Therefore, metabolic acidosis cannot be observed after ultra-long endurance events. In contrast, a respiratory alcalosis is the common finding.